Assessment of Nutritional Status and Dietary Practices Among School-Going Adolescents in Rural and Urban Area: A Comparative Study: Assessment of dietary practices among school-going adolescents - Zainab, Yumna; Noreen, Sana; Rizwan, Bahisht; Ume Farwa, Syeda; Abbas, Wajeeha; Naveed, Javeria; Tariq, Anosha; Babar, Sibgha; Ali, Masooma (Pakistan Journal of Health Sciences, 2022)
The nutritional status of adolescents is of utmost importance as this stage of life accounts for the massive growth and maturation of the human body. Substandard nutritional status during adolescence is a significant determinant of health outcomes later in life. Objectives: To assess and compare the nutritional status and dietary habits of school-going adolescents in rural and urban areas. Methods: A cross-sectional study was conducted to assess the nutritional status of adolescents from different schools in rural and urban areas. A total of 100 participants were selected through the non-probability sampling technique. Participants were assessed using a standardized questionnaire that included a food frequency questionnaire (FFQ), socio-demographic, nutritional knowledge and eating habits. Data was then entered and analyzed using SPSS version 24.0. Among 100 participants, 50 were male, and 50 were female. All-inclusive participants were between 14-17 years of age. Results: In rural areas, 40% of the students were underweight, whereas, in urban areas, only 26% were underweight. However, the percentage of normal body mass index was equal. The prevalence of the overweight category was two times greater in urban areas, 16%, compared to 8% in the rural area. Mostly urban area students consumed more junk rather than natural foods and homemade foods, which were more common among rural students. Comparatively, rural students were more undernourished and leaner. Conclusion: Nutritional status of students from both areas was different from each other by a considerable margin but collectively was insufficient and poor.